Neuroprotection by Encephalomyelitis: Rescue of Mechanically Injured Neurons and Neurotrophin Production by CNS-Infiltrating T and Natural Killer Cells - Hammarberg, H. (J Neurosci, 2000)
In experimental autoimmune encephalomyelitis (EAE), CD4(+) self-reactive T cells target myelin components of the CNS. However, the consequences of an autoaggressive T cell response against myelin for neurons are currently unknown. We herein demonstrate that EAE induced by active immunization with an encephalitogenic myelin basic protein peptide dramatically reduces the loss of spinal motoneurons after ventral root avulsion in rats. Both brain-derived neurotophic factor (BDNF)- and neurotrophin-3 (NT-3)-like immunoreactivities were detected in mainly T and natural killer (NK) cells in the spinal cord. In addition, very high levels of BDNF, NT-3, and glial cell line-derived neurotrophic factor mRNAs were present in T and NK cell populations infiltrating the CNS. Interestingly, bystander recruited NK and T cells displayed similar or higher neurotrophic factor levels compared with the EAE disease-driving encephalitogenic T cell population. High levels of tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) mRNAs were also detected, and both these cytokines can be harmful to several types of CNS cells, including neurons. However, treatment of embryonic motoneuron cultures with TNF-α or IFN-γ only had a deleterious effect in cultures deprived of neurotrophic factors. These results suggest that the potentially neurodamaging consequences of severe CNS inflammation are curbed by the production of several potent neurotrophic factors in leukocytes.